129k views
8 votes
copy each expression below in simplify it using the order of operations a: 6+4(2+3)² b: (6+4)(2+3) c: 6+4x2³+3​

2 Answers

10 votes

a:

6+4(5)^2 = 6 + 100 = 606

b:

(10)(5) = 50

c:

6+4x8+3 = 6+32+3 = 41

User Finley Adams
by
5.4k points
9 votes

Answer:

A. 106

B. 50

C. 41

Explanation:

a: 6+4(2+3)²


\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}


6+4\cdot \:5^2


6+4\cdot \:25


6 + 100


106

Hence, [A] = 106

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

b: (6+4)(2+3)


\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}


10\left(2+3\right)


10\cdot5

50

Hence, [B] = 50

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

c: 6+4x2³+3​


Follow\:the\:PEMDAS\:order\:of\:operations


6+4\cdot \:8+3


6+32+3

41

Hence, [C} = 41

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

!Lenvy!

User Shawnee
by
4.7k points